PENERAPAN REGRESI LINEAR BERGANDA UNTUK MEMPREDIKSI DIABETES SECARA DINI - Sari, Ayunita; Putri, Dian Utami (JURNAL TEKNISI, 2023)
Diabetes is a long-lasting disease characterized by high or above normal blood sugar (glucose) levels. Lack of public information about diabetes and constraints on the problem of hospital costs make people reluctant to check themselves at the health center, therefore this can help people find information early on to better maintain their health so they don't suffer from diabetes. Predictive efforts are needed to find out the approximate outcome of diagnosing diabetes in someone early on with Pregnancies, Glucose (sugar), BloodPressure (blood pressure), SkinThickness, Insulin, BMI (Weight), DiabetesPedigreeFunction, Age (Age). Furthermore, predictions use the regression method where there are 7 more methods including (1) Linear Regression, (2) Support Vector Regression - Linear, (3) Support Vector Regression - RBF, (4) Decision Tree Regression, (5) Random Forest Regressor, ( 6) Gradient Boosting Regression, (7) NLP Regressor applied in this study. The aim of the research is to be able to determine the best regression method based on 7 regression methods with the best accuracy value that will be used in the deploy process to predict the outcome of diagnosing diabetes in someone from an early age. Decision tree regression as the best method among other regression methods in 4 accuracy tests with ratios of 90:10, 80:20, 70:30 and 60:40.Keywords: diabetes, decision tree, regressionDiabetes merupakan penyakit yang berlangsung lama ditandai dengan kadar gula (glukosa) darah yang tinggi atau diatas normal. Kurangnya informasi masyarakat mengenai penyakit diabetes dan kendala masalah biaya kerumah sakit membuat masyarakat enggan untuk memeriksakan dirinya ke puskesmas, oleh karena itu ini dapat membantu masyarakat mengetahui informasi sejak dini untuk lebih menjaga kesehatan agar tidak menderita diabetes. Diperlukannya upaya prediksi untuk mengetahui perkiraan hasil diagnose diabetespada seseorang sejak dini dengan Pregnancies, Glucose (gula), BloodPressure (tekanan darah), SkinThickness , Insulin, BMI (Berat Badan), DiabetesPedigreeFunction, Age (Umur). Selanjutnya prediksi menggunakan metode regresi dimana terdapat 7 metode lagi meliputi (1) Linear Regression, (2) Support Vector Regression Linear, (3) Support Vector Regression RBF, (4) Decision Tree Regression, (5) Random Forest Regressor, (6) Gradient Boosting Regression, (7) NLP Regressor yang diterapkan dalam penelitian ini. Tujuan penelitian untuk dapat menentukan metode regresi terbaik berdasarkan 7 metode regresi dengan nilai akurasi paling terbaik yang akan digunakan dalam proses pengolahan deploy untuk prediksi hasil diagnose diabetespada seseorang sejak dini. Decision tree regression sebagai metode terbaik diantara metode regresi lainnya dalam 4 pengujian akurasi dengan rasio 90:10, 80:20, 70:30 dan 60:40.Kata Kunci: diabetes, decision tree, regresi